2020
DOI: 10.1093/cercor/bhaa157
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Seizure Susceptibility After Repetitive Concussion Results from Oxidative Stress, Parvalbumin-Positive Interneuron Dysfunction and Biphasic Increases in Glutamate/GABA Ratio

Abstract: Chronic symptoms indicating excess cortical excitability follow mild traumatic brain injury, particularly repetitive mild traumatic brain injury (rmTBI). Yet mechanisms underlying post-traumatic excitation/inhibition (E/I) ratio abnormalities may differ between the early and late post-traumatic phases. We therefore measured seizure threshold and cortical gamma-aminobutyric acid (GABA) and glutamate (Glu) concentrations, 1 and 6 weeks after rmTBI in mice. We also analyzed the structure of parvalbumin-positive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 73 publications
1
19
2
Order By: Relevance
“…Hippocampal CA1 hyperexcitability and epileptogenesis caused by changes in the sodium channel expressed in inhibitory PV + interneurons have been previously reported (Liautard, Scalmani et al 2013). While histological and electrophysiological studies have previously identified PV + interneurons to be selectively altered in experimental models of rodent TBI (Nichols, Bjorklund et al 2018, Carron, Sun et al 2020, Figueiredo, Harbert et al 2020, MacMullin, Hodgson et al 2020), we could not identify a specific sodium channel responsible for the observed changes in CA1 interneurons following concussion. Using NEURON model of a CA1 PV + interneuron (specifically basket cell), we observed a reduction in the sodium channel window current which in turn may also affect resurgent and/or persistent currents generated by voltage-gated sodium channels (for review, see (Eijkelkamp, Linley et al 2012)).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Hippocampal CA1 hyperexcitability and epileptogenesis caused by changes in the sodium channel expressed in inhibitory PV + interneurons have been previously reported (Liautard, Scalmani et al 2013). While histological and electrophysiological studies have previously identified PV + interneurons to be selectively altered in experimental models of rodent TBI (Nichols, Bjorklund et al 2018, Carron, Sun et al 2020, Figueiredo, Harbert et al 2020, MacMullin, Hodgson et al 2020), we could not identify a specific sodium channel responsible for the observed changes in CA1 interneurons following concussion. Using NEURON model of a CA1 PV + interneuron (specifically basket cell), we observed a reduction in the sodium channel window current which in turn may also affect resurgent and/or persistent currents generated by voltage-gated sodium channels (for review, see (Eijkelkamp, Linley et al 2012)).…”
Section: Discussioncontrasting
confidence: 69%
“…Hippocampal CA1 hyperexcitability and epileptogenesis caused by changes in the sodium channel expressed in inhibitory PV + interneurons have been previously reported (Liautard, Scalmani et al 2013). While histological and electrophysiological studies have previously identified PV + interneurons to be selectively altered in experimental models of rodent TBI (Nichols, Bjorklund et al 2018, Carron, Sun et al 2020, Figueiredo, Harbert et al 2020, MacMullin, Hodgson et al 2020, we could not identify a specific sodium channel responsible for the observed changes in CA1 interneurons following concussion.…”
Section: Concussion As a Risk For Development Of Post-traumatic Epile...contrasting
confidence: 70%
“…Cohorts of wild‐type control mice were included in this analysis, some of which have previously been published. 29 , 30 Wild‐type mice on both pure C57BL/6J and mixed (129S4/SvJae, C57BL/6J, and CBA) backgrounds were used. 31 Ages of mice were grouped as follows, in accordance with widely accepted guidelines: pup (P0 to P21), juvenile (3–6 weeks), young adult (6–12 weeks), mature adult (13 weeks to 6 months), middle‐aged adult (10–14 months), and old‐aged adult (over 18 months).…”
Section: Methodsmentioning
confidence: 99%
“…This may reflect two aspects of the influence of these neurons on cortical activity. On the one hand, their main function is to support the regularity of discharges within the gamma frequency range (Sohal et al., 2009 ), with inhibitory effects on irregular and abnormal overexcitation; on the other hand, they provide supportive preservation of neuronal activities in states of energy deficiency during and after seizures (MacMullin et al., 2020 ). In this article, however, the expected more specific and stronger correlation with changes in gamma band power has not been distinguished, so in this case, the influence of PV+ neurons might be much broader.…”
Section: Discussionmentioning
confidence: 99%